THE IMPLEMENTATION OF EFFICIENT TRADE MATRIX AND GOLD RESERVE REQUIREMENT FOR COMMODITY TRADE AMONG ASEAN COUNTRIES - nurul anisak (Tazkia Islamic Finance and Business Review, 2016)
Objective - This study attempts to implement the efficient trade matrix among five selected ASEAN countries and its settlement by the gold reserve requirements through Multi-Bilateral Payments Arrangement (MBPA).Methods – The study is a qualitative research with analytic description. The purpose of this qualitative-descriptive study is to simulate the implementation of gold in the Multi-Bilateral Payment Arrangement among ASEAN countries using the current trade data.Results – This paper argues that the Southeast Asian countries can solve the problem through their internal coordination, particularly in terms of trade. One of the efforts is to reduce even eliminate the market risk by using the efficient payment arrangement.Conclusions – The study implied that the quantity amount of gold required to settle the trade balance will be reduced from the early gross payment. However, the ASEAN countries need to strengthen the cooperation among them through maximizing the trade relationship.